Impostor Phenomenon and Its Relationship to Self-Esteem Among Students at an International Medical College in the Middle East: A Cross Sectional Study - Naser, Maryam Jameel; Hasan, Nebras Ebrahim; Zainaldeen, Manal Hasan; Zaidi, Ayesha; Mohamed, Yusuf Mahdi Ahmed Mulla Hasan; Fredericks, Salim (Frontiers in Medicine, 2022)
The atmosphere of constant scrutiny of academic ability that prevails in medical colleges may leave some students at risk of expressing feelings of intellectual fraudulence and phoniness. Impostor phenomenon (IP) traits have been associated with anxiety, depression, job dissatisfaction, and poor professional performance. Internationally trained junior doctors exhibit stronger IP feelings than colleagues trained within their own country of citizenship. These feelings may develop during student life. International universities are diverse and complex environments where students may be emersed in a cultural milieu alien to their societies of origin, leading to feelings of isolation. Individuals with IP traits often perceive themselves as the “only one” experiencing this phenomenon, resulting in further isolation and negative self-evaluation, especially among women and underrepresented minorities. IP has also been linked to low self-esteem among students. This study assessed the prevalence of IP and its relationship to self-esteem among students at a campus of a European medical college with a large international student body situated in the Middle East. The self-administered questionnaires: Clance's Impostor Phenomenon Scale (CIPS) and Rosenberg's Self-Esteem Scale (RSES) were completed by 290 medical students (58.3% females). Participants' median (range) age was 19 years (16–35). Students were of 28 different nationalities; the largest proportions were from Gulf Corporation Council (GCC) countries. The prevalence of low self-esteem was 18.6%, while 45.2% of the students demonstrated traits suggestive of IP. There was a strongly negative correlation between CIPS and RSES (r = −0.71). No significant gender differences were found in IP. Similarly, no differences in IP were found when comparing between age groups, previous experience in higher education or year of study. Multivariate analysis showed that students from GCC countries had higher levels of self-esteem relative to students from other regions. Low self-esteem was a strong predictor of IP. Country of origin may influence students' self-esteem studying in international university settings.